Homopolar Induction in the Concept of the Scalar- Vector Potential (Global Journal of Science Frontier Research, 2018)
The Homopolar induction was discovered by Faraday more than 200 years ago, but also up to now the physical principles of the operation of some constructions of unipolar generators remain obscure. There were the attempts to explain the work of such generators by action on the moving charges of Lorentz force, but it turned out that there are such constructions, in which to explain their operating principle thus is impossible. It is in the present work shown that the concept of the scalar-vector potential, which assumes the dependence of the scalar potential of charge on its relative speed, makes it possible to explain the work of all existing types of unipolar generators. from the day of discovery by Faradayhomopolar induction this article appears first and thus far of only, where the true reasons for this phenomenon are reflected.
Keywords: law of the induction of faraday; lorentz force; homopolar induction; unipolar generator; scalar- vector potential